Proposed Criteria and Judgments for Assuring the Quality of Academic Programmes in Arab Higher Education - Ali AbdulGhani Yaghi (University of Science and Technology, Yemen, 2015)
It can be fairly said that there were two pioneering projects for assuring the quality of academic programmes in the Arab world. The first was launched by Al Hussein Fund for Excellence (HFE) in Jordan (2000 - 2010) and targeted programmes in Jordanian universities only, while the second was launched by the Regional Bureau of Arab States in the UNDP and targeted programmes selected from universities representing many Arab countries. The two projects were then followed, in the Arab region, by various national and regional commissions and networks that aimed at assuring the quality of higher education programmes. This paper briefly discusses the methodology, criteria and judgments adopted in each of the two projects. It then proposes new criteria with new structured judgments for assessing the quality of academic programmes in the Arab region. The proposed model (criteria and judgment) was a result of a continuous discussion and research conducted by Al Hussein Fund for Excellence, with other regional and international experts, aiming at developing the model that was followed and implemented by HFE over the last ten years. The new proposed criteria focus special attention on the academic standards of a programme in terms of its objectives, intended learning outcomes and structure and organization of its curriculum.  The suitability of the curriculum and its structure for achieving the desired objectives of the program, together with the teaching and learning environment and measures taken by the provider to ensure that students achieve the learning outcomes, are also assessed. Besides the descriptive assessment of each domain of the criteria and standards, the new proposed judgments offer numeric assessment that are structured to provide a transparent method for categorizing and ranking academic programmes.